Separatist Creditors’ Rights In Handling Bankruptcy Assets - Siregar, Dahris (DE’RECHTSSTAAT, 2025)
Law Number 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations (PKPU) protects the rights of creditors, particularly separatist creditors. It also regulates the administration and settlement of bankruptcy assets and determines whether or not the administration and settlement of bankruptcy assets has protected separatist creditors. Normative law research is the methodology used in this study. A normative theoretical examination of the principles, rules, and procedures governing Indonesian bankruptcy law is the goal of this research. The findings of the research indicate that creditors can receive a fair distribution of assets when debts are settled through insolvency institutions. Separatist creditors can suffer losses due to not meeting the legal requirements of collateral, especially those contained in Article 59 of Law No. 2004, Paragraph I of Article 55 and Paragraphs 1 and 3 of Article 56, which regulate the postponement of execution and restrictions on the period of execution of collateral. The curator must provide the list of bankruptcy assets to the court in accordance with Law No. 37 of 2004, especially paragraph 1 of Article 55 given its connection to the Law on Guarantees, backed up by the justifications for requesting the Supervisory Judge’s approval or the court designation, which has the ability to protect separatist creditors from their rights guaranteed by the Law.